The biodiversity dose-response curve translates theory and practice from ecological restoration into research and clinical priorities for fecal microbiota transplantation - Orr, Matthew R. (Frontiers in Medicine, 2022)
Discoveries of the beneficial effects of gut microbiota have led to efforts to cultivate healthy gut flora to treat disease. The field of ecological restoration specializes on reestablishment of desired species in disturbed ecosystems, which suggests that it may be applicable to microbe restoration in the gut. Common language can lower barriers to interdisciplinary insights. Here I introduce the concept of a “biodiversity dose-response curve” to translate ideas from ecological restoration into research and clinical priorities for fecal microbiota transplantation (FMT). The curve is based on a relationship between ecosystem structure, measured as species diversity found in both nature and gut ecosystems, and ecosystem function, which are the measurable parameters that contribute to ecosystem and human health. I explain why the biodiversity dose-response curve may follow the ecological model of a “rivet-redundancy” relationship, in which the overlap of multiple organisms’ functional contributions to a system mask the impact of initial losses of diversity, but, at a certain level of loss, function declines sharply. (Imagine an airplane that flies with a few rivets missing, until it loses enough to fail.) The biodiversity dose-response curve indicates that seemingly healthy individuals may be suboptimal donors; it highlights the importance of recipient diet in FMT success; and it introduces the concept of “passive restoration” into the field of gut medicine. These insights, which may help to explain low success rates of FMT in the treatment of non-Clostridium dificile conditions, are less apparent in the absence of interdisciplinary integration.